DCMQA, a caffeoylquinic acid derivative alleviates NMDA-induced neurotoxicity via modulating GluN2A and GluN2B-containing NMDA receptors in vitro. (September 2020) - Yang, Yue; Gao, Huan; Liu, Wenwu; Jiang, Xiaowen; Shen, Zexu; Li, Xiang; Ren, Tianshu; Xu, Zihua; Cheng, Gang; Zhao, Qingchun
Abstract: Compound DCMQA (4, 5-O-dicaffeoyl-1-O-[4-malic acid methyl ester]-quinic acid) is a natural caffeoylquinic acid derivative isolated from Arctium lappa L. roots. Caffeoylquinic acid derivatives have been reported to possess neuroprotective effects through inhibiting oxidative stress and apoptosis in vitro. However, whether DCMQA exerts protective effects on N -methyl-D-aspartate (NMDA)-induced neurotoxicity and the underlying mechanism has not been elucidated. In this study, the results indicated that pretreatment of DCMQA prevented the loss of cell viability and attenuated the LDH leakage in SH-SY5Y cells exposed to NMDA. Hoechst 33342 staining and Annexin V-PI double staining illustrated that DCMQA suppressed NMDA-induced morphological damage and neuronal apoptosis. Moreover, DCMQA inhibited NMDA-mediated Ca 2+ influx, excessive intracellular ROS generation and loss of mitochondrial membrane potential (MMP). Western blot analysis showed that DCMQA attenuated the Bax/Bcl-2 ratio, release of cytochrome c as well as expression of caspase-9 and caspase-3. Besides, DCMQA down-regulated GluN2B-containing NMDA receptors (NMDARs) and up-regulated GluN2A-containing NMDARs, promoted the disruption of nNOS and PSD95 as well as activation of CaMK II-α. Furthermore, computational docking study indicated that DCMQA possessed a good affinity for NMDARs. These results indicated that DCMQA protects SH-SY5Y cells against NMDA-induced neuronal damage. In addition, the underlying mechanisms of DCMQA-mediated neuroprotection are associated with modulating NMDARs and disruption of nNOS-PSD95 as well as the activation of CaMK II-α. Highlights: DCMQA exerts neuroprotective effects against NMDA-induced neuronal apoptosis. Modulation of GluN2A and GluN2B-containing NMDARs contributes to DCMQA-mediated neuroprotection. Disruption of nNOS and PSD95 is implicated in the neuroprotective effects of DCMQA.